ANALISIS HUBUNGAN PENUTUP/PENGGUNAAN LAHAN DENGAN TOTAL SUSPENDED MATTER (TSM) KAWASAN PERAIRAN SEGARA ANAKAN MENGGUNAKAN DATA INDERAJA - Parwati, Ety; Trisakti, Bambang; Carolita, Ita; Kartika, Tatik; Harini, Sri; Dewanti, Ratih (Institut Teknologi Sepuluh Nopember, 2006)
Segara Anakan and its surrounding which is located in Cilacap Regency Central of Java, is the study area for this research. This region, like other estuaries, has a unique ecosystem which is protected and surrounded by the mangrove forest that can cause very dynamic development. In the upland, there are three big rivers flow; Citanduy, Cibeureum, and Cimeng. The main issue in this region is that the lagoon to become narrowing because of rapid sedimentation process. Landsat MSS, TM, and ETM of the years 1978, 1995, 1998, and 2003 are remote sensing data used in this research. An analysis in term of correlation between landuse/landcover changes and sedimentation was carried out by looking at their changes in the upper land especially along the rivers that have big contribution to the sedimentation in the lagoon. The result shows that there is high relation between landuse/landcover changes in the upper land and sedimentation around the lagoon.